The role of marketing communications in influencing the promotion and visibility of tourist destinations: A systematic literature review - Hardiyanto, Dhony; Wijaya, Mahendra; Satyawan, Agung (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: This systematic literature review (SLR) analyzes tourism marketing communication, uncovering successful strategies and emerging trends. It covers branding, digital marketing, social media, and more, while assessing effectiveness across various contexts. Research Methodology:  Systematic literature review was conducted by analyzing 31 journals related to marketing communication, which addressed strengths, limitations, biases, and gaps, and answered the research objectives and questions coherently. Results: The discussion of the research questions revealed insights into the impact of digital marketing communication strategies on the promotion and visibility of tourist destinations (RQ 1). It is evident that digital strategies utilizing various online channels, real-time updates, and search engine optimization play a pivotal role in enhancing destination visibility. The influence of marketing communication on tourists' decision-making processes (RQ 2) was illuminated, highlighting the role of marketing communication at every stage of the traveler's journey. Marketing communication significantly shaped tourists' decisions, from creating awareness to post-trip engagement. Cultural, social, and environmental factors were found to influence the effectiveness of marketing communication strategies in sustainable and responsible tourism (RQ 3). Sensitivity to local culture, commitment to sustainability, and messaging of eco-friendly practices were pivotal in aligning communication with responsible tourism. Limitations: The literature reviewed may be limited to a specific time period; therefore, trends and strategies that emerged after that period were not covered. This affects the relevance of future findings in digital marketing communication. Contribution: This SLR contributes to a comprehensive understanding of marketing communication strategies in tourism, offering insights into their impact, relevance, and alignment with responsible practices.